2024
DOI: 10.1002/prp2.1169
|View full text |Cite
|
Sign up to set email alerts
|

Scopolamine regulates the osteogenic differentiation of human periodontal ligament stem cells through lactylation modification of RUNX2 protein

Ying Wu,
Pan Gong

Abstract: Periodontal ligament stem cells (PDLSCs) are important mesenchymal stem cells contributing to regenerating lost periodontal tissues and repairing bone defects. Studies on the molecular mechanism affecting the osteogenic differentiation of PDLSCs are necessary. Scopolamine (SCO) is known as a regulator of neural cell damage. The focus of the current study is on unveiling the role of SCO‐mediated molecular mechanism in the osteogenic differentiation of PDLSCs. Through CCK‐8 assay and LDH detection, we confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…Periodontal ligament stem cells are important mesenchymal stem cells contributing to regenerating lost periodontal tissues and repairing bone defects. The study showed that Scopolamine promotes the lactylation of RUNX2 at the K176 site enhances the protein stability to promote the osteogenic differentiation of PDLSCs [ 40 ].…”
Section: Physiological Functions Of Protein Lactylationmentioning
confidence: 99%
“…Periodontal ligament stem cells are important mesenchymal stem cells contributing to regenerating lost periodontal tissues and repairing bone defects. The study showed that Scopolamine promotes the lactylation of RUNX2 at the K176 site enhances the protein stability to promote the osteogenic differentiation of PDLSCs [ 40 ].…”
Section: Physiological Functions Of Protein Lactylationmentioning
confidence: 99%